Comparison of the Quality of Life after Skeletonized versus Pedicled Grafts in Coronary Artery Bypass Graft Surgery - Khan, Muhammad Shahzeb (Int J Angiol, 2015)
It remains a controversial issue whether internal thoracic artery (ITA) should be dissected in skeletonized or pedicled manner during coronary artery bypass graft (CABG) surgery. The main objective of this cohort study was to compare skeletonized versus pedicled grafts on the basis of patients' perceptions of their physical and mental well-being. Isolated nonemergent CABG patients were divided into two groups according to the type of graft used; skeletonized or pedicled. The quality of life (QOL) was measured preoperatively, 6 months postoperatively, and 12 months postoperatively for each patient using the 36-Item Short Form Health Survey tool. The main outcome variables were physical component summary (PCS) score and mental component summary (MCS) score. A total of 140 patients were included in the study with 70 patients in each group. The PCS (p-value = 0.235) and MCS (p-value = 0.239) scores of patients were similar in both the groups before CABG. The PCS and MCS scores were significantly (p-values < 0.0001) improved after CABG at 6 months in both the groups. However, the PCS and MCS scores in the skeletonized group were significantly higher (p-values < 0.0001) than the scores in the pedicled group at 6 and 12 months post-CABG. Both the harvesting techniques improve QOL significantly after CABG. However, skeletonization results in significantly better PCS and MCS scores compared with pedicled harvesting technique.